Investigating the Link between Alpha-Fetoprotein, Vitamin D, and Obesity: A Multifactorial Analysis - Ahmed Faisal Obed; Asmaa Hamza Radeef; Safa Amer Ali (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background:Obesity is a complicated and varied health concern that persists in presenting considerable issues worldwide.Alpha-fetoprotein (AFP) is a glycoprotein mostly synthesised by the foetal liver and yolk sac during gestation.The relationship between AFP and vitamin D concerning obesity is a subject of continuing investigation. Both indicators are associated with adipose tissue function and metabolism. Aim:The aim of this study is to investigate the multifactorial relationship between alpha-fetoprotein (AFP) levels, vitamin D status, and obesity in order to understand how these factors interrelate and influence each other. Methods:The study comprised fifty-nine overweight people, defined by a body mass index over 25. Another 35 individuals were selected for the control group. Measurement of serum concentrations of Serum Alpha Fetoprotein using competitive radioimmunoassay utilising the VIDAS system, and serum vitamin D through solid phase competitive sandwich enzyme-linked immunosorbent assay (ELISA). Results: The serum level of AFP was significantly higher in overweight group compered to healthy group.There is positive statistically significant correlation between age and serum level of AFP in overweight patients. There is a negative statistically significant correlation between BMI and Serum level of Vit D3 in overweight patients. Conclusions: The study explores the link between AFP, vitamin D, and obesity, revealing the pathogenesis of obesity and potential treatment targets. The study emphasizes the importance of monitoring liver health and cancer risk in overweight individuals, and the need for regulating body weight and obtaining sufficient vitamin D for overall health.